2020
DOI: 10.21273/hortsci14550-19
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of the Impact of Vascular Wilt and Soil Hypoxia on Cape Gooseberry Plants by Foliar Application of Synthetic Elicitors

Abstract: Physalis peruviana L. crops are exposed to different stress conditions that limit their productivity. Within these conditions, abiotic stress caused by water and biotic stress by Fusarium oxysporum f. sp. physali (Foph) are frequent at commercial levels. The foliar application of synthetic elicitors can be a tool to mitigate the negative impacts of these stresses. The objective of this study was to evaluate the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 80 publications
(93 reference statements)
2
17
0
Order By: Relevance
“…The parameters of chlorophyll a fluorescence are a fast and non-destructive technique that allows estimating the plant's tolerance or acclimatization to abiotic stress conditions (Chaerle et al, 2007;Kalaji et al, 2017). Parameters such as the F v /F m ratio have been used as plant acclimatization indicators to stressful conditions (Alvarado-Sanabria et al, 2017;Chávez-Arias et al, 2020). In this research, SC plants showed the lowest values of this variable, mainly in "F2000" rice plants.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The parameters of chlorophyll a fluorescence are a fast and non-destructive technique that allows estimating the plant's tolerance or acclimatization to abiotic stress conditions (Chaerle et al, 2007;Kalaji et al, 2017). Parameters such as the F v /F m ratio have been used as plant acclimatization indicators to stressful conditions (Alvarado-Sanabria et al, 2017;Chávez-Arias et al, 2020). In this research, SC plants showed the lowest values of this variable, mainly in "F2000" rice plants.…”
Section: Discussionmentioning
confidence: 88%
“…The crop stress index (CSI) and relative tolerance index (RTI) are used to determine if the treatments evaluated help to mitigate different stresses (abiotic and biotic) and have a positive effect on plant physiology (Castro-Duque et al, 2020;Chávez-Arias et al, 2020). CSI values can range between zero and one, representing the non-stressed and stressed conditions, respectively (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The mycelium spreads fast via xylem, producing microconidia that can rapidly invade the plant, generating vascular obstructions caused by hyphae that block the flow of water and nutrients (Ownley and Trigiano, 2016). In addition, the biotic stress caused by the pathogen infection impairs the plant physiology of diseased plants (Villarreal-Navarrete et al, 2017;Chaves-Gómez et al, 2020b). As a result, the visual alterations caused by the disease are chlorosis of the basal leaves, affecting later stages in the entire plant, followed by moderate to severe defoliation, and finally necrosis and death of the plant (Robles Carrión et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…physali (Foph) strain MAP5 (Laboratory of Biological Control, Agrosavia) was used as the pathogen source. The strain underwent previous morphological, molecular, and pathogenic characterization on cape gooseberry plants (Simbaqueba et al, 2018 ; Chaves-Gómez et al, 2019 ; Chávez-Arias et al, 2020 ). The pathogen was multiplied in malt extract (ME) liquid medium (Oxoid®, Thermo Fisher Scientific, Waltham, MA, United States) with constant stirring at 125 rpm, under darkness at 25°C for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, research about the interaction between water deficit and fusarium wilt incidence has also gained importance, since crop plants (such as cotton, tomato, and banana) have shown more severe disease development under water stress conditions (Ghaemi et al, 2011 ; Meddich et al, 2018 ; Orr and Nelson, 2018 ). Recent studies have been focused mainly on the effect of waterlogging and its impact on Foph incidence in cape gooseberry plants (Villarreal-Navarrete et al, 2017 ; Chávez-Arias et al, 2019 , 2020 ). Those reports concluded that waterlogging caused a higher vascular wilt incidence, and that the physiological (stomatal conductance, F v /F m ratio) and biochemical (MDA, and proline content) variables can be useful to evaluate the effect of single or combined stresses on this plant species.…”
Section: Introductionmentioning
confidence: 99%